EFEKTIVITAS INSTRUMEN HAM NASIONAL TERHADAP PERLINDUNGAN ANAK KORBAN TPPO DI KOTA KUPANG, NUSA TENGGARA TIMUR - Ganggut, Agnes Yuniatri; Fadil Mas’ud; Petronia Mersiana Damai; Jami Djeru (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Human trafficking is one of the most complex forms of human rights violations, as it involves the exploitation of the dignity and freedom of individuals, especially children. Human trafficking is one of the most complex forms of human rights violations. This study aims to examine the effectiveness of national human rights instruments in protecting child victims of human trafficking in Kupang City, East Nusa Tenggara. A descriptive-qualitative research approach was employed by combining literature review, analysis of laws and regulations, and interviews with relevant stakeholders, including civil society, law enforcement, and child protection institutions.The findings indicate that human trafficking cases in Kupang City have not yet fully benefited from the use of national human rights instruments. Weak inter- agency coordination, limited resources, inadequate protection and recovery facilities for victims, and low public understanding of children's rights are the main factors influencing this condition. Although various legal frameworks such as Law No. 21 of 2007 on the Eradication of Human Trafficking and Law No. 35 of 2014 on Child Protection are available, their implementation at the regional level still faces institutional and cultural barriers. This study emphasizes the importance of strengthening a human rights-based child protection system by increasing public awareness of the risks of human trafficking, enhancing cross-sector collaboration, and improving government capacity. To provide comprehensive and sustainable protection for child victims of human trafficking, legal, social, and educational strategies must be effectively integrated.